Vorislamische Grundrißformen nach altjüdischen Quellen - Stern, Shimon (ERDKUNDE, 1989)
The model of an oriental town contains characteristics of Islamic times. These include the bazaar (Suq), the Friday mosque and the large square around the mosque. However, other characteristics pre-date them. Ancient Jewish sources show that street plans (cul-de-sacs), as well as the form and seclusion of the houses are of pre-Islamic origin.